Exploring Social Responsibility in Sports Management: A Comprehensive Literature Review - Pfister, Matthias (Journal of Knowledge Management Practice, 2024)
This study examines the integration of social responsibility within sports management, highlighting its unique challenges compared to traditional corporations. Through a systematic literature review of 51 studies from 1993 to 2021, this paper identifies key challenges and opportunities in promoting Corporate Social Responsibility (CSR) in sports. The analysis reveals diverse theoretical frameworks and methodological approaches, with stakeholder theory being most prominent. Findings emphasize the need for theoretical coherence and highlight three primary clusters of CSR in sports: societal impacts, ethical governance, and diversity inclusion. The review underscores the influential role of athletes and the complexities of addressing corruption and racism in sports management. It identifies the influence of celebrity status, stakeholder engagement, and the integration of sustainable practices as crucial factors in promoting positive societal change. It also addresses the complexities of ethical behavior, cultural diversity, and stakeholder management in sports. This study contributes to the discourse on sports management by offering insights into the multifaceted challenges and opportunities inherent in promoting sustainability and ethical conduct in the sports industry.